The Implementation of Participatory Action Research (PAR) to Enhance Basic Iqro' Reading Skills among Children in Alue Buloh Village - Rauzatul Jannah; M. Rezki Andhika; Suharman; Nacsiatul Fadhila (Universitas Nahdlatul Ulama Surabaya, 2025)
This community service initiative was implemented at Balee Carong in Alue Buloh Village, an isolated rural community experiencing significant educational access limitations due to damaged bridge infrastructure. The geographical constraints had severely restricted children's opportunities for supplementary education, including tutoring programs and religious studies. The program aimed to enhance children's fundamental skills in Iqro' reading, memorization of short surahs and daily prayers, along with basic literacy and numeracy competencies through participatory and engaging learning methodologies. Employing Participatory Action Research (PAR) as its foundational framework, the project positioned university students as both facilitators and collaborative change agents working directly with the community. Over a 45-day implementation period, educational activities were delivered through interactive approaches including game-based learning, singing, storytelling, and various creative exercises tailored to local context. Implementation results demonstrated remarkable progress in both religious and academic dimensions among participating children. Quantitative and qualitative assessments revealed that the majority of children showed substantial advancement in Iqro' reading proficiency, with significant increases in memorization of Islamic prayers and short chapters from the Quran. Concurrently, participants exhibited marked improvement in basic reading, writing, and arithmetic capabilities. The program culminated in two significant closing events: a